Research Progress on the Genetic and Molecular Mechanisms of Cucumber (Cucumis sativus L.) Powdery Mildew Resistance - Jian Wang; Yuyan Sun; Shengjun Zhou; Yuqiang Zhu; Luyao Gao; Xin Wang; Wenqi Dong; Jihong Tan; Huasen Wang; Peng Zhang (Horticulturae)
As a common fungal disease, powdery mildew (PM) is one of the main diseases that harm the growth and development of cucumbers. Understanding the types of pathogenic fungus and analysis of the genetic and molecular mechanisms of cucumber resistance to PM at the molecular level are important when breeding disease-resistant varieties. The present review summarizes the hazards, prevention, and control of PM, and it discusses resistance inheritance rules, molecular markers, quantitative trait locus (QTL) mapping, gene cloning, omics, and gene editing technology, providing research insights on cucumber breeding varieties resistant to PM.